2021
DOI: 10.3390/cancers13215536
|View full text |Cite
|
Sign up to set email alerts
|

Management of VEGFR-Targeted TKI for Thyroid Cancer

Abstract: Recent advances in the development of multitarget tyrosine kinase inhibitors (MTKIs), which mainly target the vascular endothelial growth factor receptor (VEGFR), have improved prognoses and dramatically changed the treatment strategy for advanced thyroid cancer. However, adverse events related to this inhibition can interrupt treatment and sometimes lead to discontinuation. In addition, they can be annoying and potentially jeopardize the subjects’ quality of life, even allowing that the clinical outcome of pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 118 publications
(188 reference statements)
0
10
0
Order By: Relevance
“…In fact, TKIs exert immunomodulatory properties that may shift the tumor microenvironment from immunosuppressive to immune-permissive [ 28 ]. However, different life-threatening off-target toxicities have been described, including thyroid dysfunctions, cardiovascular events, bleeding, proteinuria/renal impairment, hepatotoxicity, gastrointestinal perforations, metabolic and wound healing complications with an impact on quality of life and monitoring strategies [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, TKIs exert immunomodulatory properties that may shift the tumor microenvironment from immunosuppressive to immune-permissive [ 28 ]. However, different life-threatening off-target toxicities have been described, including thyroid dysfunctions, cardiovascular events, bleeding, proteinuria/renal impairment, hepatotoxicity, gastrointestinal perforations, metabolic and wound healing complications with an impact on quality of life and monitoring strategies [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Angiogenesis is affected by vascular endothelial growth factor (VEGF), and studies have shown that the expression of VEGF gene is upregulated in thyroid cancer, especially in ATC. Tyrosine kinase inhibitors of VEGF receptors are currently used as targeted therapies for ATC patients [ 43 , 45 , 46 ]. The treatment of ATC cell lines with BI-847325 may decrease tumor angiogenesis by reducing VEGF expression (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Thyroid cancer aggressiveness is associated with increased angiogenesis and the expression of VEGF/VEGFR, PDGF/PDGFR, and EGF/EGFR [43,44]. In differentiated thyroid cancer, VEGFR and VEGFR-2 are overexpressed and contribute to tumor progression and aggressiveness.…”
Section: Vegfmentioning
confidence: 99%